2019
DOI: 10.1111/josh.12758
|View full text |Cite
|
Sign up to set email alerts
|

School Health Program: Impacting Physical Activity Behaviors Among Disadvantaged Students

Abstract: BACKGROUND: Children from disadvantaged backgrounds are more apt to experience lower availability of nutritious foods, lack opportunities to exercise, and lack access to recreational facilities, and thus, are more likely to be obese and at greater risk for developing chronic diseases. We review school health education programs' impact on physical activity behaviors among disadvantaged students. METHODS:The inclusion criteria of the study were articles: published in English with full text between 2011 and 2017;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 36 publications
1
17
0
1
Order By: Relevance
“…As briefly reviewed here, there have been various but similar models suggesting the components or factors of school health, thus, the question is if there are instruments to measure these factors. Measuring the factors of school health is important; it helps the health specials, school nurses, school principals, teachers, parents, politicians, and other stakeholders to realize what they need to improve in order to effectively promote student health, which in turn leads to better educational outcomes ( Best, Oppewal & Travers, 2018 ; Rahman et al, 2018 ) promotes public health ( Kolbe, 2019 ; Birch & Auld, 2019 ), improves mental health ( Deborah, 2019 ; Redfern et al, 2019 ; Holt, 2020 ), increases health equity ( Peng et al, 2019 ; Gonzĺez, Etow & De La Vega, 2019 ), promotes general health ( Boroumandfar et al, 2015 ; Krok-Schoen et al, 2018 ; Mishra et al, 2018 ), prevents diseases ( Akihiro et al, 2017 ; Park et al, 2017 ; Jihene et al, 2015 ), promotes physical activities ( Kelly et al, 2019 ; Dai, 2019 ), healthier nutritional choices ( Anita, 2019 ; Shrestha et al, 2019 ), and increases student’s safety ( Voon & Ariff, 2019 ; Chalupka & Anderko, 2019 ; Mannathoko, 2019 ), among many other benefits.…”
Section: Introductionmentioning
confidence: 99%
“…As briefly reviewed here, there have been various but similar models suggesting the components or factors of school health, thus, the question is if there are instruments to measure these factors. Measuring the factors of school health is important; it helps the health specials, school nurses, school principals, teachers, parents, politicians, and other stakeholders to realize what they need to improve in order to effectively promote student health, which in turn leads to better educational outcomes ( Best, Oppewal & Travers, 2018 ; Rahman et al, 2018 ) promotes public health ( Kolbe, 2019 ; Birch & Auld, 2019 ), improves mental health ( Deborah, 2019 ; Redfern et al, 2019 ; Holt, 2020 ), increases health equity ( Peng et al, 2019 ; Gonzĺez, Etow & De La Vega, 2019 ), promotes general health ( Boroumandfar et al, 2015 ; Krok-Schoen et al, 2018 ; Mishra et al, 2018 ), prevents diseases ( Akihiro et al, 2017 ; Park et al, 2017 ; Jihene et al, 2015 ), promotes physical activities ( Kelly et al, 2019 ; Dai, 2019 ), healthier nutritional choices ( Anita, 2019 ; Shrestha et al, 2019 ), and increases student’s safety ( Voon & Ariff, 2019 ; Chalupka & Anderko, 2019 ; Mannathoko, 2019 ), among many other benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Combined, this suggests the initial levels of MVPA were high leaving minimum room for improvement and the children could be seen as ‘resilient’ in the context of socioeconomic disadvantage. Second, while socially disadvantaged communities are often challenging environments to work in, Dai et al (2019) cite one of the factors likely to influence the success of PA programs with socially disadvantaged children is parental involvement [26]. Lack of participation in the parent workshops, despite being heavily publicized through the school newsletters, individual flyers sent to every child’s home and the Parents and Friends Association, attendance may have been influenced by the announced closure of a manufacturing (car) plant, a major employer of many parents in the school community, with the resulting unemployment impacting on the level of engagement of the parents/guardians.…”
Section: Discussionmentioning
confidence: 99%
“…Programs and policies to increase PA using multicomponent approaches through schools are currently being implemented in numerous countries, such as Ireland, Finland, France, Germany, and Switzerland [25]. A recent review of school-based programs aiming to increase PA amongst disadvantaged children found that multicomponent school-based health education programs which were comprised of culturally appropriate PA, a choice of activities which aimed to enhance motivation along with parent involvement, were all potential factors related to higher PA levels among students from disadvantaged background [26].…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript to be reviewed school principals, teachers, parents, politicians, and other stakeholders to realize what they need to improve in order to effectively promote student health, which in turn leads to better educational outcomes (Best, Oppewal & Travers, 2018;Rahman et al, 2018) promotes public health (Kolbe, 2019;Birch & Auld, 2019), improves mental health (Deborah, 2019;Redfern et al, 2019;Holt, 2019), increases health equity (Peng et al, 2019;Gonzalez, Etow & De La Vega, 2019), promotes general health (Boroumandfar et al, 2015;Krok-Schoen et al, 2018;Mishra et al, 2018), prevents diseases (Akihiro et al, 2017;Park et al, 2017;Jihene, 2015), promotes physical activities (Kelly et al, 2019;Dai, 2019), healthier nutritional choices (Anita, 2019;Shrestha, 2019), and increases student's safety (Voon & Ariff, 2019;Chalupka & Anderko, 2019;Mannathoko, 2019), among many other benefits.…”
Section: Introductionmentioning
confidence: 99%